2017
DOI: 10.1111/and.12910
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cigarette smoking on human seminal parameters, sperm chromatin structure and condensation

Abstract: Considerable debate still exists regarding the effects of cigarette smoking on male fertility. This work aimed to explore effects of cigarette smoking on semen parameters and DNA fragmentation on 95 infertile patients who were divided into infertile male nonsmokers (45) and infertile male smokers (50). Smokers were subdivided according to a number of cigarettes smoked per day into mild (≤10), moderate (11-20) and heavy smokers (≥21). Semen analysis, sperm chromatin condensation integrity with aniline blue stai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 45 publications
(53 reference statements)
4
48
0
5
Order By: Relevance
“…A recent study showed that current male smoking and passive smoking in either partner was not associated with reduced fecundability (Wesselink et al, ). Mostafa et al () observed a dose‐dependent relationship between the amount and duration of smoking and its impact on semen parameters, while the seminal function was worse in heavy smokers and participants with long smoking duration. Similarly, the decline in semen quality was more pronounced in heavy (>20 cigarettes/day) and moderate (10–20 cigarettes/day) smokers compared to mild smokers (1–10 cigarettes/day) (Sharma et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that current male smoking and passive smoking in either partner was not associated with reduced fecundability (Wesselink et al, ). Mostafa et al () observed a dose‐dependent relationship between the amount and duration of smoking and its impact on semen parameters, while the seminal function was worse in heavy smokers and participants with long smoking duration. Similarly, the decline in semen quality was more pronounced in heavy (>20 cigarettes/day) and moderate (10–20 cigarettes/day) smokers compared to mild smokers (1–10 cigarettes/day) (Sharma et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Infertile men can have in their seminal plasma, elevated levels of ROS and decreased antioxidant concentrations (Iwasaki & Gagnon, ; Mahfouz, Sharma, Sharma, Sabanegh, & Agarwal, ). Contributing factors to OS, either from an endogenous or exogenous source, include genitourinary infections, varicocele, metabolic syndromes, cigarette smoking, alcohol abuse, recreational drug abuse, ionising radiation, mobile phone use, psychological stress, strenuous exercise, spinal cord injury and environmental pollution (Adams, Galloway, Mondal, Esteves, & Mathews, ; Agarwal, Prabakaran, & Allamaneni, ; Bisht & Dada, ; Condorelli, Russo, Cologero, Morgia, & La Vignera, ; De Lamirande, Leduc, Iwasaki, Hassouna, & Gagnon, ; Harlev, Agarwal, Gunes, Shetty, & du Plessis, ; Mostafa et al., ; Sharma, Harlev, Agarwal, & Esteves, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to take confounders into consideration since previous studies have shown that a diversity of conditions and factors, such as smoking, alcohol use, age, and BMI also influence sperm parameters, which is in line with the induction of excessive oxidative stress. [ 26–29 ] Although, less research is performed on paternal influences on pregnancy outcomes, we assume that the same confounding factors should be considered.…”
Section: Resultsmentioning
confidence: 99%